LEGAL FRAMEWORKS OF SPECIAL AND INCLUSIVE EDUCATION - Paiva, Olga Maria de Souza Leão; Lima, Marilurdes Menezes de; Azevedo, Mauro; Galindo, Rafael Marques Moraes; Pessoa, Matheus Gelaski da Silva; Cantalice, Maria Betânia do Nascimento; Coutinho, Diogenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
The main objective of this paper is to bring the child to the center of the agenda of discussions involving this context, the "three institutions of the citizen": Family, School and Church, even she - the child - does not figure as a priority on the public policy agenda of the three spheres of power (federal, states and municipalities). And also the kindergarten to the economy, culture, history, politics, health and environment, placing the care and education of early childhood as a strategic point for human and social development. This is our challenge!